2022
DOI: 10.3390/ijms232113622
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synovial CD14 mRNA Expression and Proportion of CD14high Subsets in Early-Stage Hip Osteoarthritis: Propensity Matched Score Analysis

Abstract: The pathophysiology of early-stage hip osteoarthritis (EOA) is not fully understood. Although a previous study in an age-unmatched cohort reported that the number of macrophages was increased in knee EOA compared to late OA (LOA), it remained unclear whether increased macrophages in EOA accurately reflect EOA pathology. We investigated the differences in CD14 expression levels between EOA and LOA using age-unmatched and -matched cohorts. Synovial tissues were obtained from 34 EOA (Tönnis grades 0 and 1) and 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Importantly, the contribution of CD39−CD55+ cells may be more significant in the early stages of OA, where synovitis plays a crucial role in driving pain [44]. As OA advances, the inflammatory response tends to diminish [45,46], potentially diminishing the impact of this fibroblast subset in late-stage OA. To fully elucidate the role of fibroblast subtypes across different OA stages, further investigations utilizing synovial tissue from early OA patients are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the contribution of CD39−CD55+ cells may be more significant in the early stages of OA, where synovitis plays a crucial role in driving pain [44]. As OA advances, the inflammatory response tends to diminish [45,46], potentially diminishing the impact of this fibroblast subset in late-stage OA. To fully elucidate the role of fibroblast subtypes across different OA stages, further investigations utilizing synovial tissue from early OA patients are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Toll-like receptor (TLR) signal on monocytes induces production of proinflammatory cytokines/ chemokines and transmission of pain signals. [ 28 , 29 ] A recent study has shown that the typical response of CD14CD16 monocytes to knee synovial derived mediators is a key target for overcoming the onset and progression of osteoarthritis. [ 30 ] TLR pathway plays an important role in OA inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The femoral bone contour served as the starting point for JSW measurement, while the reference line for the tibial mid-coronal plane was established by connecting the medial and lateral edges of the tibia. Pain evaluations, including VAS-R and VAS-M, were conducted during the preoperative periods using the standard 10-point VAS, where each point represents 10 mm on the scale (ranging from 0 mm for no pain to 100 mm for the worst imaginable pain) [50]. Clinical assessments were performed at our outpatient facility a month before each surgical intervention.…”
Section: Correlation Between Proportion Of Entpd1+cd55+ Cells and Oa ...mentioning
confidence: 99%